1999
DOI: 10.1161/01.hyp.33.1.499
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Mechanisms Underlying a Novel Salt-Sensitive Hypertensive Model Induced by Sensory Denervation

Abstract: Abstract-A novel model of hypertension recently developed in our laboratory shows that neonatal degeneration of capsaicin-sensitive sensory nerves renders a rat responsive to a salt load with a significant rise in blood pressure. To determine the role of the renin-angiotensin system and the sympathetic nervous system in the development of hypertension in this model, newborn Wistar rats were given capsaicin 50 mg/kg SC on the first and second days of life. Control rats were treated with vehicle. After they were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 22 publications
4
47
3
Order By: Relevance
“…These data show that selective knockdown of neuronal TRPV1 enhances prohypertensive effects induced by salt loading and that pressor effects of TRPV1 shRNA may be mediated, at least in part, by enhancement of the sympatho-excitatory response. We have previously shown that neonatal degeneration of TRPV1-expressing sensory nerves increased salt sensitivity of arterial pressure as these rats grew into adulthood [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . However, the systemic sensory denervation used in these previous studies precluded us from making conclusions about whether the observed effect was due to the removal of TRPV1 or other proteins co-expressed in the same nerves innervating any specific organs or tissues [21,22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data show that selective knockdown of neuronal TRPV1 enhances prohypertensive effects induced by salt loading and that pressor effects of TRPV1 shRNA may be mediated, at least in part, by enhancement of the sympatho-excitatory response. We have previously shown that neonatal degeneration of TRPV1-expressing sensory nerves increased salt sensitivity of arterial pressure as these rats grew into adulthood [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . However, the systemic sensory denervation used in these previous studies precluded us from making conclusions about whether the observed effect was due to the removal of TRPV1 or other proteins co-expressed in the same nerves innervating any specific organs or tissues [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, defining the role of TRPV1-positive sensory nerves in the regulation of blood pressure and salt sensitivity will be useful. We have shown previously that the degeneration of TRPV1-expressing sensory nerves throughout the neonatal body by subcutaneous injection of capsaicin, a selective TRPV1 agonist, leads to increased salt sensitivity of arterial pressure, indicating that TRPV1-positive sensory nerves play a counter-regulatory role against salt-induced increases in blood pressure [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . The underlying mechanism of anti-hypertensive effects of TRPV1 may involve its counter-balancing role against the activation of the renin-angiotensin-aldosterone system [7][8][9] , sympathetic nervous system [10] , endothelin system [11,12] , superoxide generation system [13,14] , and epithelial sodium transporters [15] .…”
Section: Introductionmentioning
confidence: 99%
“…On the first and second days of life, neonatal rats received capsaicin, 50 mg/kg s.c., as described. 1,2,7,8 Control rats were treated with equal volumes of vehicle solution (5% ethanol, 5% Tewwn 80 in saline). After three weeks, male rats were divided into four groups, pair-fed different sodium diets, and subjected to following treatments for three weeks: control + high sodium diet (4%, CON-HS), capsaicin pretreatment + normal sodium diet (0.5%, CAP-NS), capsaicin pretreatment + high sodium diet (CAP-HS), capsaicin pretreatment + high sodium diet + candesartan cilexetil (10 mg/kg/per day by oral gavage) (CAP-HS-CAN).…”
Section: Animalsmentioning
confidence: 99%
“…Furthermore, we have previously shown that development of salt-sensitive hypertension induced by sensory denervation can be prevented by the AT 1 -receptor antagonist losartan. 2 However, the molecular basis for the antihypertensive effect of losartan in this model is unknown. The goal of the current study is to test the hypothesis that the circulating and/or tissue renin angiotensin systems are activated in response to a high-salt intake and contribute to the elevation of BP induced by salt load in this model.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation